Probabilistic projections of future warming and climate sensitivity trajectories. Issue 1 (23rd July 2021) - Goodwin, Philip
Abstract: Projections of future global mean surface warming for a given forcing scenario remain uncertain, largely due to uncertainty in the climate sensitivity. The ensemble of Earth system models from the Climate Model Intercomparison Project phase 6 (CMIP6) represents the dominant tools for projecting future global warming. However, the distribution of climate sensitivities within the CMIP6 ensemble is not representative of recent independent probabilistic estimates, and the ensemble contains significant variation in simulated historic surface warming outside agreement with observational datasets. Here, a Bayesian approach is used to infer joint probabilistic projections of future surface warming and climate sensitivity for shared socio-economic pathway (SSP) scenarios. The projections use an efficient climate model ensemble filtered and weighted to encapsulate observational uncertainty in historic warming and ocean heat content anomalies. The probabilistic projection of climate sensitivity produces a best estimate of 2.9°C, and 5th–95th percentile range of 1.5–4.6°C, in line with previous estimates using multiple lines of evidence. The joint projection of surface warming over the period 2030–40 has a 50% or greater probability of exceeding 1.5°C above preindustrial for all SSPs considered: 119, 126, 245, 370 and 585. Average warming by the period 2050–60 has a >50% chance of exceeding 2°C for SSPs 245, 370 and 585. These results imply that global warming is no longer likely to remain under 1.5°C, even with drastic and immediate mitigation, and highlight the importance of urgent action to avoid exceeding 2°C warming.